FERMENTASI DEDAK PADI UNTUK PAKAN AYAM DI KAMPUS IV BANGKO DESA BOBANAIGO MADEHUTU - Emy Saelan; Dwi Nur Happy Hariyono; Sri Lestari; Yunus Syafie (Bajang Institute, 2024)
Fermentation of rice bran for chicken feed at Bangko Campus IV, Bobaigo Madehutu Village is carried out with the aim of training chicken breeders, including free-range, broiler and Bangkok chicken breeders, in providing quality feed that meets nutritional standards for growth, so that they can produce optimal production.The methods used in implementing this activity to achieve the objectives and overcome the problems faced by farmers include training in the cultivation of free-range chickens and broilers and the implementation of vaccinations, training in making fermented bran feed, formulating feed according to the age and needs of the livestock as well as guidance to livestock groups which is carried out on an ongoing basis. , monitoring and evaluation carried out on assisted livestock groups.The results of implementing this service activity are (1) The assisted livestock group has the ability to improve the planning of free-range chicken cultivation business activities; (2) Have the ability to handle the initial arrival of native chicken DOC; (3) Have skills in processing feed through fermentation technology, (4) Have skills in formulating feed ingredients according to livestock needs, and (5) Have skills in carrying out vaccinations